Representasi Ironisme Kemanusiaan dalam Industri Musik Populer AS - AYU AMALIA (Komunikator, 2013)
Music is one of media product which is not able to be separated from Political Economy of Media even though it is packaged as leisure time entertainment product. Music which is particularly in Alternative subgenre is not far from its main genre which is Rock. In fact, this subgenre has a solid and prominent fan base which consists of young people who enjoy dynamic and fast-tempo music which tells the struggle of youngsters in their life. Ironically, the tragic incidents which surround the band personnel of ‘The All-American Rejects’ are used to increase the popularity of their single entitled ‘Move Along’. Keywords: Popular Music, the Political Economy of Media, Commodification, Discourse Analysis